2021
DOI: 10.2174/1871526520666200820093924
|View full text |Cite
|
Sign up to set email alerts
|

Determining Serum Levels of IL-10 and IL-17 in Patients with Low Back Pain Caused by Lumbar Disc Degeneration

Abstract: Background: Low Back pain (LBP) is a common health problem that affects different aspects of a person's life. Degeneration of the intervertebral disc is a major cause of LBP. Interleukin-17 (IL-17) is a pro-inflammatory cytokine. In contrast, interleukin-10 (IL-10) prevents the occurrence of immune over-stimulation by inhibiting inflammation. The purpose of this study was to evaluate the serum levels of these cytokines in LBP patients and in the control group. Methods: In a case-control study 87 patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine impaired regulation of insulin signaling might promote the development of and pain sensation with diabetic neuropathy, which can be alleviated by its functional restoration [266][267][268][269]. e interleukin-(IL-) 17 pathway plays a crucial role in cellular mechanisms of pain pathogenesis and maintenance in various diseases including multiple sclerosis, prostatitis, intervertebral disk degeneration, femoral head osteonecrosis, and neuropathy; its inhibition might block the generation and persistence of pain [270][271][272][273][274][275][276][277][278][279][280][281][282]. Arachidonic acid metabolism is associated with the generation and secretion of diverse biomolecular substances Evidence-Based Complementary and Alternative Medicine responsible for the induction of inflammation and pain, and it is mainly involved in the mechanisms of action of NSAIDs [283][284][285][286][287][288].…”
Section: Functional Enrichment Investigation Of Jakyak-gamchomentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine impaired regulation of insulin signaling might promote the development of and pain sensation with diabetic neuropathy, which can be alleviated by its functional restoration [266][267][268][269]. e interleukin-(IL-) 17 pathway plays a crucial role in cellular mechanisms of pain pathogenesis and maintenance in various diseases including multiple sclerosis, prostatitis, intervertebral disk degeneration, femoral head osteonecrosis, and neuropathy; its inhibition might block the generation and persistence of pain [270][271][272][273][274][275][276][277][278][279][280][281][282]. Arachidonic acid metabolism is associated with the generation and secretion of diverse biomolecular substances Evidence-Based Complementary and Alternative Medicine responsible for the induction of inflammation and pain, and it is mainly involved in the mechanisms of action of NSAIDs [283][284][285][286][287][288].…”
Section: Functional Enrichment Investigation Of Jakyak-gamchomentioning
confidence: 99%
“…The innate immune system can further secrete IL-17 ( 109 ). IL-17 is associated with inflammation, and increasing evidence has shown that IL-17 is involved in the occurrence and progression of IVDD ( 110 112 ). There is no IL-17 in normal AF and NP, and elevations of IL-17 can be detected in degenerative structures ( 113 ).…”
Section: Regulation Of the Inflammatory Microenvironmentmentioning
confidence: 99%
“… 112 Moreover, serum levels of IL‐10 are reported to be lower in LBP patients than controls. 113 Zhou et al 114 demonstrated that IL‐10 led to a reduction in pain sensitivity in the spinal dorsal horn induced by formalin injection. Following injury to the sciatic nerve and DRG in a mouse model, the expression level of IL‐10 was increased.…”
Section: Immune Cytokines Involved In Ivd Degenera...mentioning
confidence: 99%
“…IL‐10 treatment suppresses the expression of IL‐1β and TNF‐α as a consequence of the impeded development of inflammatory responses 112 . Moreover, serum levels of IL‐10 are reported to be lower in LBP patients than controls 113 . Zhou et al 114 demonstrated that IL‐10 led to a reduction in pain sensitivity in the spinal dorsal horn induced by formalin injection.…”
Section: Immune Cytokines Involved In Ivd Degeneration/herniationmentioning
confidence: 99%